Nasal obstruction and productive cough in a 12 years old girl in Basrah, Iraq; the diagnosis of Kartagener syndrome is established. - Ziyad Tariq Malghooth; Haider Kadhem Saeed (Zien Journals, 2022)
Kartagener syndrome (KS) is an autosomal recessive genetic disorder characterized by ciliary dyskinesia that causes defects in the action of ciliary movement affecting the nose, paranasal sinuses, lung and others. The syndrome comprises of triad situs inversus, chronic sinusitis with some times nasal polyposis and bronchiectasis. Kartagener syndrome regarded as a subset of the primary ciliary dyskinesia which manifested early in life with frequent respiratory infections, frequent sinus infections, frequent ear infections, chronic nasal congestion and Sino nasal polyposis and male infertility
Keywords: Kartagener syndrome; immotile cilia syndrome; Basrah; bronchiectasis